How do you solve this problem using substitution and then check it?: y= -3x-2  2x+5y=16

(2) Answers

You have to get a variable by itself like in here... Y is itself so in the other equation or we can say second one you just have to sub it in... Like 2x+5(-3x-2)=16 2x-15x-10=16 Now you just have to subtract 2 from 15, because of the same variable that is (x) So -13x-10=16 Take 10 to the other side means add from the both sides, that will get you at -13x=26 So now x= -2 Remember you added because it was -10 if it would be a positive 10 then you have to subtract it from both of the sides but since here it was negative so you just added them up Hope i helped


We have the variable y so lets substitute y=-3x-2 2x+5y=16 2x+5y=16 2x+5(-3x-2)=16 2x-15x-10=16 -13x=26 x=-2 y=-3x-2   =-3(-2)-2   =4 2x+5y=16 2(-2)+5(4)=16 -4+20=16 16=16

Add answer